Nephrology providers’ perspective and use of mortality prognostic tools in dialysis patients - Jennifer Bergeron; Christina Marchese; Colton Jensen; Sean Meagher; Amanda G. Kennedy; Bradley Tompkins; Katharine L. Cheung (BMC Nephrology)
Abstract Background Mortality prognostic tools exist to aid in shared decision making with kidney failure patients but are underutilized. This study aimed to elucidate nephrology providers’ practice patterns and understand barriers to prognostic tool use. Methods Nephrology providers (8 physicians and 2 nurse practitioners) at an academic medical center underwent semi-structured interviews regarding their experience and perspective on the utility of mortality prognostic tools. Common themes were identified independently by 2 reviewers using grounded theory. Three six-month mortality prognostic tools were applied to the 279 prevalent dialysis patients that the interviewed providers care for. The C statistic was calculated for each tool via logistic regression and subsequent ROC analysis. Nephrology providers reviewed the performance of the prognostication tools in their own patient population. A post interview reassessed perspectives and any change in attitudes regarding the tools. Results Nephrology providers did not use these mortality prognostic tools in their practice. Key barriers identified were provider concern that the tools were not generalizable to their patients, providers’ trust in their own clinical judgement over that of a prognostic tool, time constraints, and lack of knowledge about the data behind these tools. When re-interviewed with the results of the three prognostic tools in their patients, providers thought the tools performed as expected, but still did not intend to use the tools in their practice. They reported that these tools are good for populations, but not individual patients. The providers preferred to use clinical gestalt for prognostication. Conclusion Although several well validated prognostic tools are available for predicting mortality, the nephrology providers studied do not use them in routine practice, even after an educational intervention. Other approaches should be explored to help incorporate prognostication in shared-decision-making for patients receiving dialysis.